COST-BENEFIT ANALYSIS OF RIGID PAVEMENT ROAD CONSTRUCTION USING EXPONENTIAL, NPV, AND ERR METHODS (CASE STUDY: CIMANYING-JIPUT ROAD SECTION, PANDEGLANG, BANTEN) - Ruchiyat, Ficka; Prabowo, Yudi Setio (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
This study aims to analyze the economic feasibility of rigid pavement road construction through a comprehensive cost-benefit analysis using Net Present Value (NPV), Economic Rate of Return (ERR), and exponential methods, with a case study on the Cimanying-Jiput road section in Pandeglang, Banten.  This research employs a quantitative approach where data collection was conducted through field surveys to obtain primary data and documentation from relevant agencies to gather secondary data. The economic feasibility assessment uses NPV and ERR methods, where a project is considered economically feasible if it yields an NPV greater than zero and an ERR exceeding the Bank Indonesia discount rate of 4.60%. The calculation results show that the Net Present Value (NPV) is Rp. 5,687,857,786, and the Economic Rate of Return (ERR) is 15%. Both indicators demonstrate that the benefits generated exceed the costs incurred. Based on the cost-benefit analysis using NPV and ERR methods, the construction project for the Cimanying-Jiput road section is economically viable and recommended for implementation. The positive NPV and ERR values above the discount rate indicate that the project will generate substantial economic benefits for the community and transportation system in the region.